Ludwig Senfl Motets for Six and Eight Voices, Canons - Gasch, Stefan (Hollitzer, 2023)
The fourth volume of the New Senfl Edition (NSE) completes the new edition of Ludwig Senfl's motets, including Senfl's famous reworking of the Ave, Maria ... Virgo serena by Josquin Desprez, three motets with an unusually large scoring for eight voices (presumably composed for state events), as well as several compositions conceived as pure canons, demonstrating Senfl's lifelong interest in canonic structures. In addition to the musical editions, the volume offers numerous illustrations, as well as critical reports discussing each work, providing comprehensive information on the texts, plainchant models, an evaluation of the sources, as well as the context of the works' history. Volume 1: https://e-book.fwf.ac.at/o:1556 Volume 2: https://e-book.fwf.ac.at/o:1694 Volume 3: https://e-book.fwf.ac.at/o:1728 Volume 4: https://e-book.fwf.ac.at/o:1842